The Impact of the Global Financial Crisis on the Labor Market: The Case of the Philippines - Jenny D. Balboa; Melalyn C. Mantaring (Philippine Institute for Development Studies (PIDS), 2011)
The Global Financial Crisis of 2007 was one of the worst crises that hit the world economy since the Depression era. For the next two years, the crisis created waves of economic contraction that affected developed and developing economies. The Philippines was not spared from this crisis. As an export-oriented economy, the global financial crisis created serious strains in the domestic economy when its top export destination for both goods and services suffered a downturn. Inflow of foreign direct investment also slowed down, further creating a slack in economic growth, and consequently leading to less employment opportunities in the country. Several studies analyzed how the global economic crisis was transmitted to the domestic economy. This paper culled the results of these studies with the end goal of understanding the impact of the global financial crisis on the Philippines' human resources. It also tackled the government's response to mitigate the impact of the crisis in the labor market and the lessons learned from these interventions. This paper is part of the APEC project on Human Resource Impacts of the Global Economic Crisis, which aims to assess the human resource impacts of the global economic crisis.
Keywords: 330; human resources; Philippines; Philippine economy; global financial crisis; Finanzkrise; Beschäftigungseffekt; Arbeitsmarktpolitik; Wirtschaftliche Anpassung; Philippinen